Krytyczna analiza propozycji dekryminalizacji przestępstwa zniesławienia - Sikora, Marcin (Studia Prawa Publicznego, 2024)
There is a noticeable view in the social space about the need to decriminalise the offence of defamation. Such a position is unfounded and is not based on factual and scientific grounds and, in particular, does not take into account the constitutional principle of proportionality. The historical and comparative legal analysis also does not give grounds to admit that the proponents of decriminalisation of defamation are right, as the criminal law protection of honour and good name has a long tradition, firm foundations, which are also taken into account and continued by most European states in the present times. The removal of Articles 212–215 of the Criminal Code from the legal system would violate the positive obligation of the state to ensure adequate protection of honour and good name. Advocates of the decriminalisation of defamation refer their demands primarily to the value of freedom of expression, while the right to maintain honour and good name is often overlooked. Freedom of speech does not represent a higher value than honour and good name. The current civil law system is incapable of adequately protecting the values listed in Article 47 of the Polish Constitution against groundless slander, in particular because of the low effectiveness of the enforcement of monetary claims and the lack of adequate and enforceable non-monetary sanctions. In the longer term, essentially uncontrolled freedom of speech would become a source of much damage to legally protected goods and would initiate another discussion on the proper protection of honour and reputation. A certain category of defamation is so socially dangerous that the criminal law protection of the value of honour, good name and the right to privacy should continue. Persons in the professions of public trust, entrepreneurs are particularly exposed to the negative consequences of defamation, and the social harm increases in the case of defamation carried out in the Internet space, where it is difficult to mount a substantive defence and the content of the defamation is visible to a large audience.